Peningkatan Kemampuan Bahasa Inggris dalam Melakukan Bisnis pada Staff Yayasan Chalisaturahmi Luqman Halim - Soraya Grabiella Dinamika; Yoni Rahayu; Muhammad Muslim Nasution (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2024)
This Community Service (PKM) activity aims to disseminate useful knowledge related to improving English language skills in doing  business to staff and teachers at Yayasan Chalisaturahmi Luqman Halim, Gg. Sei Sipirok, Padang Bulan Selayang I, Kec. Medan Selayang, Medan City. The PKM implementation method is carried out with participation, partnership, networking and process-oriented which includes socialization, demonstration, teaching, explaining and direct practice. Participants in this activity amounted to 25 people who were staff and teachers at the foundation.  The results of the activity were obtained through direct observation. The results and targets achieved in this service activity are to provide knowledge to the participants, especially the staff and teachers at the Chalisaturahmi Luqman Halim Foundation which can help improve English language skills in doing  business. Thus, this activity has made a real contribution in increasing understanding and developing the potential and ability of the participants in using English in accordance with the assistance provided. The questionnaire test results from the pre-test and post-test, showed an N-gain of 0.81, categorized as a high gain (g > 0.7). Therefore, it can be seen that the participants' understanding and knowledge of the use of English in running an  business has increased. This shows that the material, exposure and assistance presented by the service implementation team are quite well understood and accepted by the training participants.